Avaliação da eficiência de filtros anaeróbios na remoção de coliformes fecais e ovos de helmintos - Cavalcante, Fernanda Lima (2007)
The technology of anaerobic reactors for sanitary wastewater treatment has been extensively developed in Brazil, and today it is practically consolidated. They present several advantages, such as low construction and operating costs, and low sludge production, the anaerobic reactors are an attractive alternative to minimize problematic lack of basic sanitation in urban areas, and also of the rural areas. The anaerobic filters have been widely used in Brazil. It produces an effluent with low concentration of organic matter and solids suspended, besides conserving the nutrients, therefore, it is good for use in irrigation, but the practice must be associated with knowledge of the pathogens presence. The main objective of this study was to evaluate the efficiency of anaerobic filters in removal faecal coliforms and helminth eggs, and to verify if the effluent can be used for agricultural purposes, according to the World Organization of Health (WHO, 1989). The protocol used to enumerate helminths eggs was the modified Bailenger method, (Ayres and Mara, 1996) recommended by WHO for evaluation of raw effluent and treated effluent. The membrane filtration method was utilized to determine the concentrations of faecal coliforms. Three different systems of sewer treatment composed by anaerobic filters were analyzed. The results, in a general analysis, showed that all the researched systems reached a larger removal than 93% to helminth eggs, resulting in an effluent with smaller average than 1 egg/L. One of these systems, Sistema RN, reached a larger removal than 99%, confirming the good performance of the anaerobic filters in removal helminths eggs. Even with low concentrations of eggs in the influent, the filters were capable to remove this parameter efficiently. About faecal coliforms, it was observed for all the researched systems an effluent with 106 CFU/100mL. The high concentrations to faecal coliforms in the effluent just allow reuse for restricted irrigation, in agreement with the guidelines of WHO. Although the researched systems have not removed faecal coliforms efficiently, the results indicated a good efficiency of the anaerobic filters in removal helminth eggs